Fulfill psychological contract promises to manage in-demand employees. Issue 5 (3rd August 2015) - Rodwell, John; Ellershaw, Julia; Flower, Rebecca
Abstract : Purpose: – The purpose of this paper is to explore the impact of three components of the psychological contract (i.e. obligations, fulfillment and breach) and the individual characteristic negative affectivity (NA) onto three key outcomes, namely, job satisfaction, organizational identification and psychological distress. Design/methodology/approach: – Questionnaires were completed by 222 Australian nurses and midwives from a medium-sized metropolitan Australian hospital. The response rate for the study was 39 percent. Findings: – Structural equation modeling revealed that perceptions of psychological contract fulfillment were positively linked to organizational identification and job satisfaction, while psychological contract breach was negatively linked to these outcomes. NA was negatively linked to job satisfaction and positively linked to psychological distress. Psychological contract obligations were not associated with any of the employee outcomes. Research limitations/implications: – Psychological contract fulfillment is an important driver of employee satisfaction and organizational identification and the findings highlight the importance of including NA in psychological contract research. The occupation and context, being in-demand employees, appeared to neutralize the impact of one dimension of the psychological contract, employer promises and obligations. Practical implications: – Explicitly managing employees' psychological contracts by focussing on fulfilling realistic promises will enable managers to improve employee outcomes and facilitate employees embracing their organization. Originality/value: – This study is one of the first to explore all three components of the psychological contract. These results may assist in the development of strategies to retain in-demand employees such as nurses, particularly highlighting the need to make and fulfill realistic promises.